2003
DOI: 10.1016/s0378-4371(02)01903-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between the probability distribution of returns in the Heston model and empirical data for stock indexes

Abstract: We compare the probability distribution of returns for the three major stock-market indices (Nasdaq, S&P500, and Dow-Jones) with an analytical formula recently derived by Drȃgulescu and Yakovenko for the Heston model with stochastic variance. For the period of 1982-1999, we find a very good agreement between the theory and the data for a wide range of time lags from 1 to 250 days. On the other hand, deviations start to appear when the data for 2000-2002 are included. We interpret this as a statistical evidence… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(38 citation statements)
references
References 5 publications
4
34
0
Order By: Relevance
“…The intraday time lags were chosen at multiples of 5 minutes, which divide exactly the 6.5 hours (390 minutes) of the trading day. The interday returns are as described in [4,5] for time lags from 1 day to 1 month = 20 trading days.…”
Section: Data Analysis and Discussionmentioning
confidence: 99%
“…The intraday time lags were chosen at multiples of 5 minutes, which divide exactly the 6.5 hours (390 minutes) of the trading day. The interday returns are as described in [4,5] for time lags from 1 day to 1 month = 20 trading days.…”
Section: Data Analysis and Discussionmentioning
confidence: 99%
“…Without trimming, Daniel et al (2005) have shown that the Heston model does not provide a good fit to the Dow Jones stock market index. Meanwhile, Silva and Yakovenko (2003) have verified the goodness-of-fit of the Heston model by explaining the NASDAQ, DowJones and S&P 500 indices and by documenting different results for different dataset periods. Our results show that without trimming the dataset the Heston model fits the empirical distribution of index and stock returns in the Chinese stock market well, especially for the daily log-returns.…”
Section: Introductionmentioning
confidence: 95%
“…The goodness-of-fit of the Heston model to the historical data of log-returns has been tested in studies by Dragulescu and Yakovenko (2002), Silva and Yakovenko (2003) and Daniel et al (2005), which together show mixed results regarding the performance of the Heston model. Dragulescu and Yakovenko (2002) have derived the closed form of the probability distribution of log-returns in the Heston model to show that the Heston model provides a good fit to the DowJones index returns at different time intervals.…”
Section: Introductionmentioning
confidence: 99%
“…It received a great attention in the financial literature specially in connection with option pricing [Fouque et al, 2000]. The Heston model was verified empirically with both stocks [Silva & Yakovenko, 2003, Drǎgulescu & Yakovenko, 2002 and options [Hull & White, 1987;Hull, 2004], and good agreement with the data has been found. It was also recently investigated by econophysicists [Miccichè et al, 2002;Drǎgulescu & Yakovenko, 2002;Silva et al, 2004;Bonanno & Spagnolo, 2005].…”
Section: The Heston Modelmentioning
confidence: 99%